Faktor Risiko Kejadian Kanker Payudara Pada Wanita UsiaReproduksi Di RSUD Prof. Dr. Margono Soekarjo Purwokerto Periode Januari-Juli Tahun 2011 - Desi Tri Indrayani; Heni Soetikno; Rosi Kurnia Sugiharti (Universitas Harapan Bangsa Purwokerto, 2011)
Breast cancer in many countries is the most common cancer and the mostimportant cause of death in women. In most states take a second breast cancerafter cervical cancer. It is not known with certainty the cause of breast cancer, canonly be known to certain risk factors that may be associated with breast cancer. InMargono Soekarjo Navan Hospital in 2013 In January-June of breast cancerpatients as much as 363 people. The goal is to reveal the risk factors of breast cancer in women ofreproductive age in hospitals Prof. Dr.. Margono Soekarjo Purwokerto periodfrom January to July in 2013. This study is a survey research with cross sectional analytic. The sampleused was accidental sampling, the sample in this study was 73 respondents.Analysis of the data in the study using univariate analysis.From the results of breast cancer by 36 respondents (49.3%), age> 35 years were62 respondents (84.9), parity multiparas 30 respondents (41.1), age of menarche â‰¥12 years as many as 49 respondents (67.1). Keywords: Breast Cancer, WUS, risk factors (age, parity, menarche)